EVALUASI POTENSI PENGAIRAN CALON LOKASI PERLUASAN SAWAH DI KABUPATEN TULANG BAWANG, PROVINSI LAMPUNG - Thoriq, Ahmad; Sampurna, Rizky Mulya (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
Water resources availability is a key that must be met in the paddy field extension due to water is needed for thegrowth of paddy. This study was to evaluate the potential of irrigation area for paddy field extension in TulangBawang, Lampung. The study began with the preparation phase, followed by field coordination, mobilizationteams, survey and investigation of the potential for irrigation area, processing and analysis of data field. Theresults showed that potential location of water resources in Tulang Bawang river and Pidada river with instantaneousdischarge ranged 1180-3775470 liters/ sec. Those water resources are located above the candidate sites and willbe used to irrigate candidates area varied from 74.39 to 1381.71 hectares. Driest month occurs in August about85.5 mm/month of rainfall while wet months in January about 353.33 mm/month of rainfall with annual rainfallranges from 2372 to 2539 mm/year.Keywords: irrigation, Tulang Bawang, paddy field extention